2019
DOI: 10.33594/000000035
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for Somatostatin in the Survival of Mouse Pancreatic Beta Cells

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 52 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Somatostatin also have influences on β cell. It can modulate the apoptosis and proliferation of mouse β cells in response to stress (Damsteegt et al, 2019). In addition, δ cell can direct transdifferentiate β cell therefore plays a role in β cell mass.…”
Section: δ Cell and Somatostatinmentioning
confidence: 99%
“…Somatostatin also have influences on β cell. It can modulate the apoptosis and proliferation of mouse β cells in response to stress (Damsteegt et al, 2019). In addition, δ cell can direct transdifferentiate β cell therefore plays a role in β cell mass.…”
Section: δ Cell and Somatostatinmentioning
confidence: 99%
“…In addition, the close neighborhood to the vascular system might be an advantage of the bile duct as an application way to perform re-endothelization. In the end, the re-colonization of the neoorgan with endothelial cells or other co-populations will be crucial for a successful in vivo implantation without thrombosis [28,30,33,34,36,[40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Outside of paracrine control of glucose homeostasis, delta-cell-derived somatostatin may also enhance beta-cell survival, as tissue culture of isolated mouse islets or MIN6 beta-cells in the presence of exogenous somatostatin reduced the presence of biochemical markers of stress and apoptosis caused by lipotoxicity, pro-inflammatory cytokines, or hypoglycemic conditions [108]. In addition, a recent study of human delta-cells identified the co-expression and presence in secretory granules with somatostatin of an alternatively spliced insulin gene product that encodes the insulin signal peptide and the B-chain [109].…”
Section: Delta-cellsmentioning
confidence: 99%